2013
DOI: 10.3892/mmr.2013.1501
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-143 inhibits cell migration and invasion by targeting matrix metalloproteinase 13 in prostate cancer

Abstract: Abstract. has been previously reported to be downregulated in specific types of cancer, including colorectal, bladder, oral squamous cell, pituitary, cervical, nasopharyngeal, lymphoma and prostate cancer. In the present study, the effects of miR-143 on prostate cancer cell migration and invasion were examined. Following transfection with miR-143, miR-143 expression, cell migration and invasion assays, luciferase assay and western blot analysis were conducted in prostate cancer cell lines. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…translations, which play important roles in tumor cell proliferation and neoangiogenesis. Their lowered expression rates were identified in HPV associated head and neck cancers (23)(24)(25)(26)(27)(28). In our study these miRNAs also showed lowered expression rates.…”
Section: Discussionsupporting
confidence: 48%
“…translations, which play important roles in tumor cell proliferation and neoangiogenesis. Their lowered expression rates were identified in HPV associated head and neck cancers (23)(24)(25)(26)(27)(28). In our study these miRNAs also showed lowered expression rates.…”
Section: Discussionsupporting
confidence: 48%
“…MMPs have a significant role in cancer metastasis (37). The activities of MMP-2 and MMP-9 are associated with the adhesion, invasion and angiogenesis of cancer metastasis (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of FSCN1 and SWAP70 suppresses cell migration and invasion in PCa cells, and reconstitution of these genes rescues the inhibited cell growth induced by miR-145 (44,45). In an attempt to screen targets of miR-143 involved in cell migration and invasion, metalloproteinase 13 (MMP-13) was found to be a direct target gene of miR-143 (46). Joint down-regulation of miR-143 and miR-145 also enhances cancer cell migration and invasion in vitro and in vivo through increased expression of the mesenchymal marker fibronectin and the reduced expression of E-cadherin (47), thereby promoting the EMT phenotype.…”
Section: Mir-143 and Mir-145mentioning
confidence: 98%